Method Of Detecting Tooth Root Erosion Using Ct Scan And Radiation After Receiving Orthodontic Treatment (Journal of Pharmaceutical Negative Results, 2023)
Introduction: One of the common causes of non-surgical root canal treatment failure is the inability to effectively treat all root canals due to the complex anatomy of the root canal system. The goal of root canal treatment is complete debridement of the root canal and complete removal of microorganisms and their by-products from the root canal system and effective flooding of the canal system. This goal will not be achieved without complete knowledge of root canal morphology. One of the common causes of non-surgical root canal treatment failure is the inability to effectively treat all root canals. Many studies have been presented on root canal morphology in different populations, which is certainly of great importance for endodontists and general dentists who want to perform root canal treatments.Materials and methods: In this study, 45 maxillaries first and second molar teeth were used. After disinfecting the teeth, first the number and condition of the roots were recorded for each case. The morphology of the dental canals was determined using Cone Beam Computed Tomography (CBCT) in such a way that after preparing stereotypes, the images in all three axial, sagittal, and coronal sections were morphologically evaluated with the help of Romexis software until the total number of canals for each tooth, the number of canals in each root and the morphology of the canals in one root should be determined.Results: The prevalence of three-rooted first and second molar teeth was 88% and 85%, respectively, and the prevalence of four-rooted first and second molar teeth was 4% in both cases. In 1% of the second molar teeth, the teeth had two roots. In 3% of first molars and 4% of second molars, root adhesion was observed.Conclusion: According to the results of this study, the prevalence of the fourth channel in the Iranian race is relatively high. Considering the non-invasiveness and high accuracy of CBCT to identify additional canals and the importance of discovering these canals in the success of a root canal treatment, it is recommended to use CBCT during root canal treatment in cases with anatomical complications.